Exceptional adsorption-induced cluster and network deformation in the flexible metal–organic framework DUT-8(Ni) observed by in situ X-ray diffraction and EXAFS1. Issue 26 (14th July 2015) - Bon, Volodymyr; Klein, Nicole; Senkovska, Irena; Heerwig, Andreas; Getzschmann, Jürgen; Wallacher, Dirk; Zizak, Ivo; Brzhezinskaya, Maria; Mueller, Uwe; Kaskel, Stefan
<x xml:space="preserve">Abstract</x> The "gate opening" mechanism in flexible MOF Ni2(2, 6-ndc)2dabco was elucidated in detail.